PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELASV SDN 002AIR MOLEK I KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Sabariah Sabariah; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPA'S studying student brazes V SDN 002 I. Beauteous Waters one has reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 21 students which reach points according to KKM as much 9 students with averagely brazes 63,1. Its low is yielding studies it at causes since teacher be still dominate deep learning so student involvement in learning becomes less active. Base about problem research do that action brazes with learnings model implement Contextual Teaching And Learning(CTL). This research intent to increase IPA'S studying result student brazes V SDN 002 I. Beauteous Waters School Years 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Learning Contextual Teaching And Learning (CTL), therefore gets to increase IPA'S studying result student brazes V SDN 002 I. Beauteous Waters on material Cycles water and nature scene. It can at see of thoroughness result studies individual and klasikal which gotten by student on base score which is with thoroughness percentage 42,85%, with average 63,1, worked up on i. cycle with thoroughness percentage 66,67% by average 67,38. Worked up again on cycle II.which is with thoroughness percentage 90,47% by average 78,8. On Activity learns first cycle with percentage average 73,53% worked up as 86,76% on second cycle. Student activity on first cycle with percentage average 70,37% worked up as 90,91% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement Contextual Teaching And Learning (CTL), can increase IPA'S studying result student brazes V SDN 002 I. Beauteous WatersKey word : Contextual Teaching And Learning , IPA'S Learned result